Current cancer situation in China: good or bad news from the 2018 Global Cancer Statistics? - Feng, Rui‐Mei; Zong, Yi‐Nan; Cao, Su‐Mei; Xu, Rui‐Hua (Cancer communications (London, England), 2019)
Cancer is the leading cause of death in China and depicting the cancer pattern of China would provide basic knowhows on how to tackle it more effectively. In this study we have reviewed several reports of cancer burden, including the Global cancer statistics 2018 and Cancer statistics in China, 2015, along with the GLOBCAN 2018 online database, to investigate the differences of cancer patterns between China, the United States (USA) and the United Kingdom (UK). An estimated 4.3 million new cancer cases and 2.9 million new cancer deaths occurred in China in 2018. Compared to the USA and UK, China has lower cancer incidence but a 30% and 40% higher cancer mortality than the UK and USA, among which 36.4% of the cancer‐related deaths were from the digestive tract cancers (stomach, liver, and esophagus cancer) and have relatively poorer prognoses. In comparison, the digestive cancer deaths only took up ≤ 5% of the total cancer deaths in either USA or UK. Other reasons for the higher mortality in China may be the low rate of early‐stage cancers at diagnosis and non‐uniformed clinical cancer treatment strategies performed by different regions. China is undergoing the cancer transition stage where the cancer spectrum is changing from developing country to developed country, with a rapidly increase cancer burden of colorectal, prostate, female breast cancers in addition to a high occurrence of infection‐related and digestive cancers. The incidence of westernized lifestyle‐related cancers in China (i.e. colorectal cancer, prostate, bladder cancer) has risen but the incidence of the digestive cancers has decreased from 2000 to 2011. An estimated 40% of the risk factors can be attributed to environmental and lifestyle factors either in China or other developed countries. Tobacco smoking is the single most important carcinogenic risk factor in China, contributing to ~ 24.5% of cancers in males. Chronic infection is another important preventable cancer contributor which is responsible for ~ 17% of cancers. Comprehensive prevention and control strategies in China should include effective tobacco‐control policy, recommendations for healthier lifestyles, along with enlarging the coverage of effective screening, educating, and vaccination programs to better sensitize greater awareness control to the general public.